2021
DOI: 10.1111/csp2.398
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analyses of confiscated shark fins reveal shortcomings of CITES implementations in Germany

Abstract: A three-ton shipment of dry shark fins was examined by German customs in 2017 leading to the confiscation of 405 kg of potential CITES species. We analyzed a subsample of this material (115 specimens) using DNA sequence-based identification and compared results to morphological screening of CITES species. We found a mixture of CITES regulated (4 of 11 species) and unregulated shark species. Our results demonstrate the difficulties of identifying CITES species morphologically in large fin shipments of mixed spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Various proportion of all threatened categories Fig. 2 Proportion of conservation status (IUCN status) from each sample sites step to enhance species identification accuracy (Van Houtan et al 2020;Villate-Moreno et al 2021). This approach is also more convenient for the trade monitoring staffs since it does not require extensive training in taxonomy, which is especially in shortage in Thailand and DNA based approach can be performed by outsources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various proportion of all threatened categories Fig. 2 Proportion of conservation status (IUCN status) from each sample sites step to enhance species identification accuracy (Van Houtan et al 2020;Villate-Moreno et al 2021). This approach is also more convenient for the trade monitoring staffs since it does not require extensive training in taxonomy, which is especially in shortage in Thailand and DNA based approach can be performed by outsources.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the majority Vulnerable and Endangered species identified from shark fin product indicated that we need more law enforcement and trade monitoring for those threatened species before their populations decline even further. Species identification using external morphological examination can be a first step to identify CITES-listed species or regulated species (Marshall and Barone 2016 ), however, missing key diagnostic characteristics of processed fin or even in dried fins remains problematic (Ferrette et al 2019 ; Villate-Moreno et al 2021 ), therefore we recommend DNA-based identification methods to detect threatened species and CITES-listed species in shark fin trade. A standard molecular diagnostic technique is another step to enhance species identification accuracy (Van Houtan et al 2020 ; Villate‐Moreno et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The Scalloped Hammerhead ( S. lewini ) was the second most commonly captured shark documented here. They are heavily fished worldwide either targeted or as bycatch and highly prized and traded in the global fin trade ( Villate-Moreno et al, 2021 ; Pinhal et al, 2020 ). As a result, severe population declines have occurred in different regions of the world and therefore S. lewini was evaluated as Critically Endangered in the most recent ( Rigby et al., 2019 ) assessment and is listed under the Appendix II of CITES.…”
Section: Discussionmentioning
confidence: 99%
“…50–60 miles). It is precisely due to their pelagic habits and distribution that silky sharks are directly affected by target or bycatch fisheries in open waters and their populations have severely declined during the last decades, contributing as well in great proportion to the global fin trade ( Clarke et al, 2015 ; Sánchez-de Ita et al, 2010 ; Villate-Moreno et al, 2021 ). In addition, here we report artisanal fisheries catching juveniles in coastal areas, which increases the fishing pressure on this species in the ETP.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite our primary result that shark conservation should prioritize areas within the Exclusive Economic Zones (EEZs); a conclusion supported by independent biogeographic analyses [3,4], reconstructed global fishing effort and catch [5,6], and syntheses of biotelemetry data [7]. Our analysis also responds to calls for new approaches [8,9], as official fin trade statistics have established flaws [10] that miss what remains illegal or unreported. The main criticism of Raoult et al is that our SDMs make unrealistic assumptions about fishing and that our SDMs disagree with published expert range maps (‘ERMs’, e.g.…”
mentioning
confidence: 86%